SOLUTION OF ONE CONJECTURE ON INEQUALITIES WITH POWER-EXPONENTIAL FUNCTIONS

ˇ LADISLAV MATEJÍCKA
Institute of Information Engineering, Automation and Mathematics Faculty of Chemical Food Technology Slovak University of Technology in Bratislava Slovakia EMail: matejicka@tnuni.sk Received: Accepted: Communicated by: 2000 AMS Sub. Class.: Key words: Abstract: 20 July, 2009 24 August, 2009 S.S. Dragomir 26D10. Inequality, Power-exponential functions. In this paper, we prove one conjecture presented in the paper [V. Cîrtoaje, On some inequalities with power-exponential functions, J. Inequal. Pure Appl. Math. 10 (2009) no. 1, Art. 21. http://jipam.vu.edu.au/article.php? sid=1077]. The author is deeply grateful to Professor Vasile Cîrtoaje for his valuable remarks, suggestions and for his improving some inequalities in the paper.

Solution Of One Conjecture Ladislav Matejíˇ ka c vol. 10, iss. 3, art. 72, 2009

Title Page Contents

Page 1 of 12 Go Back Full Screen Close

Acknowledgements:

Contents
1 2 Introduction Proof of Conjecture 4.6 3 4

Solution Of One Conjecture Ladislav Matejíˇ ka c vol. 10, iss. 3, art. 72, 2009

Title Page Contents

Page 2 of 12 Go Back Full Screen Close

1.

Introduction

In the paper [1], V. Cîrtoaje posted 5 conjectures on inequalities with power-exponential functions. In this paper, we prove Conjecture 4.6. Conjecture 4.6. Let r be a positive real number. The inequality (1.1) arb + bra ≤ 2
Solution Of One Conjecture Ladislav Matejíˇ ka c vol. 10, iss. 3, art. 72, 2009

holds for all nonnegative real numbers a and b with a + b = 2, if and only if r ≤ 3.

Title Page Contents

Page 3 of 12 Go Back Full Screen Close

2.

Proof of Conjecture 4.6

1 1 First, we prove the necessary condition. Put a = 2 − x , b = x , r = 3x for x > 1. Then we have

(2.1) In fact, 1 2− x
3

arb + bra > 2.
Solution Of One Conjecture

+

1 x
6x−3

1 3x(2− x )

12 6 1 =8− + 2− 3+ x x x

1 x

6x−3

Ladislav Matejíˇ ka c vol. 10, iss. 3, art. 72, 2009

1 1 6 and if we show that x > −6 + 12 − x2 + x3 then the inequality (2.1) will be x 1 fulfilled for all x > 1. Put t = x , then 0 < t < 1. The inequality (2.1) becomes

Title Page Contents

t > t3 (t3 − 6t2 + 12t − 6) = t3 β(t), where β(t) = t3 − 6t2 + 12t − 6. From β (t) = 3(t − 2)2 , β(0) = −6, and from that there is only one real t0 = 0.7401 such that β(t0 ) = 0 and we have that β(t) ≤ 0 for 6 0 ≤ t ≤ t0 . Thus, it suffices to show that t t > t3 β(t) for t0 < t < 1. Rewriting the previous inequality we get α(t) = 6 − 3 ln t − ln(t3 − 6t2 + 12t − 6) > 0. t

6 t

Page 4 of 12 Go Back Full Screen Close

From α(1) = 0, it suffices to show that α (t) < 0 for t0 < t < 1, where α (t) = − 6 ln t + t2 6 −3 t 1 3t2 − 12t + 12 − 3 . t t − 6t2 + 12t − 6

α (t) < 0 is equivalent to t2 (t − 2)2 > 0. t3 − 6t2 + 12t − 6 From γ(1) = 0, it suffices to show that γ (t) < 0 for t0 < t < 1, where γ(t) = 2 ln t − 2 + t + γ (t) = (4t3 − 12t2 + 8t)(t3 − 6t2 + 12t − 6) − (t4 − 4t3 + 4t2 )(3t2 − 12t + 12) (t3 − 6t2 + 12t − 6)2 2 + +1 t t6 − 12t5 + 56t4 − 120t3 + 120t2 − 48t 2 = + + 1. (t3 − 6t2 + 12t − 6)2 t p(t) = 2t − 22t + 92t − 156t + 24t + 240t − 252t + 72 < 0. From p(t) = 2(t − 1)(t6 − 10t5 + 36t4 − 42t3 − 30t2 + 90t − 36), it suffices to show that (2.2) q(t) = t6 − 10t5 + 36t4 − 42t3 − 30t2 + 90t − 36 > 0.
Page 5 of 12 Go Back Full Screen Close
7 6 5 4 3 2
Solution Of One Conjecture Ladislav Matejíˇ ka c vol. 10, iss. 3, art. 72, 2009

Title Page Contents

γ (t) < 0 is equivalent to

Since q(0.74) = 5.893, q(1) = 9 it suffices to show that q (t) < 0 and (2.2) will be proved. Indeed, for t0 < t < 1, we have q (t) = 2(15t − 100t + 216t − 126t − 30) < 2(40t4 − 100t3 + 216t2 − 126t − 30) = 4(t − 1)(20t3 − 30t2 + 78t + 15) < 4(t − 1)(−30t2 + 78t) < 0.
4 3 2

This completes the proof of the necessary condition. We prove the sufficient condition. Put a = 1 − x and b = 1 + x, where 0 < x < 1. Since the desired inequality is true for x = 0 and for x = 1, we only need to show that (2.3) (1 − x)r(1+x) + (1 + x)r(1−x) ≤ 2 for 0 < x < 1, 0 < r ≤ 3.
Solution Of One Conjecture Ladislav Matejíˇ ka c vol. 10, iss. 3, art. 72, 2009

Denote ϕ(x) = (1 − x)r(1+x) + (1 + x)r(1−x) . We show that ϕ (x) < 0 for 0 < x < 1, 0 < r ≤ 3 which gives that (2.3) is valid (ϕ(0) = 2). ϕ (x) = (1−x)r(1+x) r ln(1 − x) − r 1+x 1−x +(1+x)r(1−x) r − r ln(1 + x) . 1−x 1+x

Title Page Contents

The inequality ϕ (x) < 0 is equivalent to (2.4) 1+x 1−x
r

1−x − ln(1 + x) 1+x

≤ (1 − x2 )rx

1+x − ln(1 − x) . 1−x
Page 6 of 12 Go Back Full Screen Close

2 1 If δ(x) = 1−x −ln(1+x) ≤ 0, then (2.4) is evident. Since δ (x) = − (1+x)2 − 1+x < 0 1+x for 0 ≤ x < 1, δ(0) = 1 and δ(1) = − ln 2, we have δ(x) > 0 for 0 ≤ x < x0 ∼ = 0.4547. Therefore, it suffices to show that h(x) ≥ 0 for 0 ≤ x ≤ x0 , where

h(x) = rx ln(1 − x2 ) − r ln

1+x 1−x

+ ln

1+x − ln(1 − x) 1−x 1−x − ln − ln(1 + x) . 1+x

We show that h (x) ≥ 0 for 0 < x < x0 , 0 < r ≤ 3. Then from h(0) = 0 we obtain

h(x) ≥ 0 for 0 < x ≤ x0 and it implies that the inequality (2.4) is valid. h (x) = r ln(1 − x2 ) − 2r 1 + x2 3−x + 2 1−x (1 − x)(1 + x − (1 − x) ln(1 − x)) 3+x + . (1 + x)(1 − x − (1 + x) ln(1 + x))
Solution Of One Conjecture Ladislav Matejíˇ ka c vol. 10, iss. 3, art. 72, 2009

Put A = ln(1 + x) and B = ln(1 − x). The inequality h (x) ≥ 0, 0 < x < x0 is equivalent to (2.5) r(2x2 + 2 − (1 − x2 )(A + B)) ≤ 3 + 2x − x2 3 − 2x − x2 + . 1 − x − (1 + x)A 1 + x − (1 − x)B

Title Page Contents

Since 2x2 + 2 − (1 − x2 )(A + B) > 0 for 0 < x < 1, it suffices to prove that (2.6) 3(2x2 + 2 − (1 − x2 )(A + B)) ≤ 3 − 2x − x2 3 + 2x − x2 + 1 − x − (1 + x)A 1 + x − (1 − x)B

and then the inequality (2.5) will be fulfilled for 0 < r ≤ 3. The inequality (2.6) for 0 < x < x0 is equivalent to (2.7) 6x −6x −(9x +13x +5x +7x+6)A−(9x −13x +5x −7x+6)B − (3x4 + 6x3 − 6x − 3)A2 − (3x4 − 6x3 + 6x − 3)B 2 − (12x4 − 12)AB − (3x4 − 6x2 + 3)AB(A + B) ≤ 0. It is easy to show that the following Taylor’s formulas are valid for 0 < x < 1:
∞ 2 4 4 3 2 4 3 2

Page 7 of 12 Go Back Full Screen Close

A=
n=0

(−1)n n+1 x , n+1

B=−
n=0

1 xn+1 , n+1

A2 =
n=1

2(−1)n+1 n+1 AB = −

n

i=1 ∞

1 i

xn+1 ,

B2 =
n=1

2 n+1 x2n+2 .

n

i=1

1 i

xn+1 ,

n=0

1 n+1

2n+1

i=1

(−1) i

i+1

Since 4 A +B = n+1 n=1,3,5,...
2 2

n

i=1

1 i

xn+1

Solution Of One Conjecture Ladislav Matejíˇ ka c vol. 10, iss. 3, art. 72, 2009

and 4 n+1 we have A2 + B 2 =

n

i=1

1 i

4 n+1
n

1+

n−1 2

= 2,

Title Page Contents

4 n+1 n=1,3,5,...
2

i=1

1 i

xn+1
n

11 137 6 4 = 2x + x4 + x + 6 90 n+1 n=7,9,... < 2x2 +
2

i=1

1 i

xn+1

Page 8 of 12 Go Back Full Screen Close

11 4 137 6 x + x +2 xn+1 6 90 n=7,9,...

11 137 6 2x8 = 2x + x4 + x + . 6 90 1 − x2 From this and from the previous Taylor’s formulas we have (2.8) 1 1 1 A + B > −x2 − x4 − x6 − 2 3 4 x8 1 − x2 ,

(2.9)

2 2 2 A − B > 2x + x3 + x5 + x7 , 3 5 7 2x8 11 4 137 6 x + x + , 6 90 1 − x2

(2.10)

A2 + B 2 < 2x2 +

Solution Of One Conjecture Ladislav Matejíˇ ka c

(2.11)

5 A2 − B 2 < −2x3 − x5 , 3 AB < −x2 − 5 4 x 12

vol. 10, iss. 3, art. 72, 2009

Title Page

(2.12)

for

0 < x < 1.

Contents

Now, having in view (2.12) and the obvious inequality A + B < 0, to prove (2.7) it suffices to show that 6x2 − 6x4 − (6 + 5x2 + 9x4 )(A + B) + (7x + 13x3 )(B − A) + (3 − 3x4 )(A2 + B 2 ) 5 + (6x − 6x3 )(A2 − B 2 ) − (12 − 12x4 ) x2 + x4 12 5 + x2 + x4 (3 − 6x2 + 3x4 )(A + B) ≤ 0. 12 By using the inequalities (2.10), (2.11), the previous inequality will be proved if we
Page 9 of 12 Go Back Full Screen Close

show that 6x2 − 6x4 − (6 + 5x2 + 9x4 )(A + B) + (7x + 13x3 )(B − A) 11 137 6 2x8 5 + (3 − 3x4 ) 2x2 + x4 + x + − (6x − 6x3 ) 2x3 + x5 6 90 1 − x2 3 5 5 − (12 − 12x4 ) x2 + x4 + x2 + x4 (3 − 6x2 + 3x4 )(B + A) ≤ 0, 12 12 which can be rewritten as (2.13) − 35 4 377 6 19 8 137 10 x + x + x − x + 6(x8 + x10 ) 2 30 2 30 55 1 5 − (A + B) 6 + 2x2 + x4 − x6 − x8 4 2 4 + (7x + 13x3 )(B − A) ≤ 0.

Solution Of One Conjecture Ladislav Matejíˇ ka c vol. 10, iss. 3, art. 72, 2009

Title Page Contents

To prove (2.13) it suffices to show (2.14) − 8x2 − 259 4 357 6 1841 8 337 10 19 12 5 x + x + x + x − x − x14 6 20 120 420 24 12 x8 3 1 2 55 4 1 6 5 + + x + x − x − x8 1 − x2 2 2 16 8 16
1 2

Page 10 of 12 Go Back

< 0.

Full Screen Close

It follows from (2.8) and (2.9). Since 0 < x < ε(x) = −8x2 −

we have

1 1−x2

< 4 . If we show 3

259 4 357 6 1841 8 337 10 19 12 x + x + x + x − x 6 20 120 420 24 5 14 2 10 55 12 1 14 5 − x + 2x8 + x + x − x − x16 < 0, 12 3 12 6 12

then the inequality (2.14) will be proved. From x6 < x4 , x8 < x4 , x10 < x4 and x12 < x4 , we obtain that ε(x) < −8x2 − This completes the proof.
Solution Of One Conjecture Ladislav Matejíˇ ka c vol. 10, iss. 3, art. 72, 2009

19 4 7 5 x − x14 − x16 < 0. 7 12 12

Title Page Contents

Page 11 of 12 Go Back Full Screen Close

References
[1] V. CÎRTOAJE, On some inequalities with power-exponential functions, J. Inequal. Pure Appl. Math., 10(1) (2009), Art. 21. [ONLINE: http://jipam. vu.edu.au/article.php?sid=1077]
Solution Of One Conjecture Ladislav Matejíˇ ka c vol. 10, iss. 3, art. 72, 2009

Title Page Contents

Page 12 of 12 Go Back Full Screen Close

Sign up to vote on this title
UsefulNot useful